2019
DOI: 10.1108/ijrdm-08-2017-0183
|View full text |Cite
|
Sign up to set email alerts
|

Colour of food as a vector for children’s well-being

Abstract: Purpose A product colour plays an important role in consumers’ preferences. The purpose of this paper is to highlight the impact of the three-dimensional character of colour (brightness, saturation and vividness) on children’s behaviour towards a food product and as a source of well-being. Design/methodology/approach Two experiments were conducted. Study 1 was conducted with 62 children and used four visuals of syrup presenting two colours (red/green) and two variations of vividness (vivid/dim). Study 2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Although the importance of multisensory experience in food consumption has been studied intensely in the offline context (e.g. Elder and Krishna, 2012;Ezan et al, 2019;Wang, 2013;Woods et al, 2016), we find a significant gap in the literature that demonstrates the underlying mechanism of crossmodal responses when consumers make food consumption decisions in the online environment.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Although the importance of multisensory experience in food consumption has been studied intensely in the offline context (e.g. Elder and Krishna, 2012;Ezan et al, 2019;Wang, 2013;Woods et al, 2016), we find a significant gap in the literature that demonstrates the underlying mechanism of crossmodal responses when consumers make food consumption decisions in the online environment.…”
Section: Introductionmentioning
confidence: 74%
“…For example, Liang et al (2013) found that the color of a food influences perceived sweetness. Also, Ezan et al (2019) demonstrated how three dimensions of colors (e.g. saturation, brightness and vividness) influence different taste perceptions (sweet, refreshing, acid, etc.).…”
Section: Limitation and Future Studymentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, while Moore and Rideout (2007) focus on systematically examining food marketers' Web sites that target children, Ezan et al (2019) analyse a completely different research issue by focusing on the effect of colour on children's behaviour toward food.…”
Section: Key Research Areasmentioning
confidence: 99%
“…When it comes to the product, little research has focused on the effect of colour on children's evaluation of product. For instance, according to Ezan et al (2019), fruit syrup colour influences children's product attitudes and desire to consume the product. A lighter, brighter red syrup seems less cold, less bland and with a fruitier taste than dark red syrup.…”
Section: Dominant Packaging Coloursmentioning
confidence: 99%